Trust and the willingness to contribute to environmental goods in selected African countries - (:unkn) unknown (My University, 2014)
Using data from theWorld Value Survey for the period 1981–2007, this papershows that the level of trust is positively linked to the willingness to contribute to environmentalgoods in selected African countries. The results are robust to possible errorsin measuring trust, to the presence of various controls, and the potential endogeneitybias. These findings complement and extend the existing literature in the sense that theyprovide evidence on the importance of trust in improving the collective management ofnatural resources in Africa.
Keywords: African Research